Propuesta de productos turísticos a través de la herramienta digital Quick Response para el Bosque Petrificado de Puyango. - Celi Mancheno., Anahí Mishell (2023)
The object of study of this research focused on how the strategic implementation of QR codes can enhance the tourist experience, providing detailed and real-time information about tourist attractions, activities, services, and relevant cultural aspects at the destination. The main objective of this research work is to propose a tourist product using the Quick Response tool for the Petrified Forest of Puyango (BPP). To achieve this, the tourist diagnosis of the BPP was carried out, taking into account the analytical and descriptive methods and the methodology of the Guide for the development of cantonal tourism development plans by AME (Association of Ecuadorian Municipalities). Additionally, techniques such as interviews, surveys, and a strategic SWOT analysis were used, as well as instruments such as summary sheets from the Ministry of Tourism (MINTUR). Subsequently, tourist products were designed based on the MINTUR manual for creating tourist routes and circuits, taking into account the two steps: destination analysis and product design. QR codes were also created within the facilities and surroundings of the Petrified Forest of Puyango. This was concluded after consulting with the main stakeholders, the tourists who regularly visit the Petrified Forest of Puyango. They determined that there is a total willingness to use QR codes, as long as they guarantee their satisfaction and meet their needs in the different spaces and services offered. This proposal of tourist products with QR technology enriches the visitor experience at the Petrified Forest of Puyango, promoting the knowledge of this invaluable natural and cultural heritage. Finally, marketing strategies were determined for the previously created tourist products, aiming to position the Petrified Forest of Puyango as an innovative new tourist attraction. The use of QR codes proved to be positively effective, as they can reach a global audience, enhance the customer experience, streamline business processes, and provide valuable data for decision-making. The effective use of technology can be a significant competitive advantage in the current tourism industry.